Visible light self-cleaning nylon fiber as well as preparation method and application thereof
By protonating the nylon fiber and loading TCPP, the existing photocatalytic activity and insufficient adhesion in visible light are solved, and the efficient pollutant degradation and self-cleaning performance of nylon fibers under visible light are achieved.
Patent Information
- Application Number
- CN202411654230.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The existing photocatalytic materials have poor catalytic activity under visible light and have insufficient binding force with organic woven fabrics, resulting in losing their self-cleaning properties after multiple washes.
After soaking nylon fibers in acetic acid solution, protonation is performed after ionization with 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) in sodium carbonate solution at high temperature, The heating reaction is loaded with TCPP to form visible light self-cleaning nylon fibers.
The excellent pollutant degradation and self-cleaning properties of nylon fibers under visible light conditions are achieved, the stability and adhesion of the photocatalyst are improved, and the overall cost is reduced.
Smart Images

Figure CN119465629A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fiber composite material preparation, and in particular relates to a preparation method of visible light self-cleaning nylon fiber, and also relates to the visible light self-cleaning nylon fiber and application thereof. Background Art
[0002] With the rapid development of society and the improvement of living standards, clothing is not only a tool to protect the body, but also gradually becomes a manifestation of personal style and fashion. However, the cleaning and maintenance of clothing has become an issue that needs attention. Traditional washing methods not only consume a lot of water resources, but also may pollute the environment. At the same time, during the washing process, the material of clothing is easily damaged, shortening its service life. Therefore, the development of self-cleaning clothing technology has gradually become a research hotspot.
[0003] Photocatalytic technology uses light energy to excite catalysts to produce electron-hole pairs, triggering a series of chemical reactions, and is considered to be an effective strategy for achieving self-cleaning clothing. Photocatalytic materials are placed on clothing fabrics to automatically remove or lighten stains under light. Self-cleaning photocatalytic materials that have been reported include nano-TiO2, ZnO, SnO2, Ag and their hybrid materials. Among these photocatalytic materials, titanium dioxide has become a research focus due to its chemical stability, low cost and excellent photocatalytic performance. However, TiO2 only exhibits efficient catalytic activity under ultraviolet light, which limits its scope of application. Although some modified TiO2 materials show certain activity under visible light, their efficiency is generally not as good as TiO2 under ultraviolet light. In addition, due to the weak bonding force between inorganic materials and organic fabrics, the adhesion of photocatalytic materials on textiles becomes a key issue. After multiple washings, the photocatalyst may fall off or lose activity, resulting in a decrease in self-cleaning performance. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a visible light self-cleaning nylon fiber, which exhibits excellent pollutant degradation and self-cleaning properties under visible light conditions.
[0005] Another object of the present invention is to provide visible light self-cleaning nylon fibers.
[0006] The third object of the present invention is to provide the use of visible light self-cleaning nylon fiber in photocatalytic degradation of pollutants.
[0007] The technical solution adopted by the present invention is a method for preparing visible light self-cleaning nylon fiber, which is specifically implemented according to the following steps: Step 1, soaking nylon fiber in an acetic acid solution, and then stirring at a high temperature to obtain modified nylon fiber; Step 2, dissolving 5, 10, 15, 20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) in a sodium carbonate solution and stirring to ionize TCPP; Step 3, adding the nylon fiber obtained in step 1 to the mixed solution of step 2, and heating the mixture in an oil bath for reaction; Step 4, adding acetic acid solution to the nylon fiber obtained in step 3, stirring to acidify it thoroughly; Step 5, washing the nylon fiber obtained in step 4 with deionized water until the pH of the washing solution is 7; Step 6, drying the nylon fiber obtained in step 5 to obtain visible light self-cleaning nylon fiber.
[0008] The present invention is also characterized in that: In step 1, the acetic acid solution is prepared by mixing acetic acid and water in a volume ratio of 1:15; during soaking, the acetic acid solution is heated in a water bath to 40-50 o C, soaking time is 30~40min; while stirring, heat the acetic acid solution in an oil bath to 100~110 o C, stirring time is 60~80min.
[0009] In step 2, the concentration of the sodium carbonate solution is 0.1 mol / L; the stirring time is 30-40 min.
[0010] In step 3, the reaction temperature is 100-110 o C, reaction time is 120~130min.
[0011] In step 4, the acetic acid solution is prepared by mixing acetic acid and water in a volume ratio of 20:20; the stirring time is 30-40 minutes.
[0012] In step 6, the drying temperature is 100~120 o C, drying time is 90~120min.
[0013] Another technical solution adopted by the present invention is the nylon fiber prepared by the preparation method of visible light self-cleaning nylon fiber.
[0014] The third technical solution adopted by the present invention is the application of visible light self-cleaning nylon fiber in photocatalytic degradation of pollutants.
[0015] The beneficial effects of the present invention are: (1) The method of the present invention uses nylon fiber to support TCPP, which is simple and easy to operate, has the potential for large-scale production, and exhibits excellent pollutant degradation and self-cleaning performance under visible light conditions; (2) In the method of the present invention, the porphyrin molecules and the nylon fibers are bonded via ionic bonds, which have a strong interaction force and effectively improve the stability of the loaded photocatalyst. In addition, the nylon fibers significantly reduce the amount of photocatalyst used and are easy to recycle, thereby reducing the overall cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 is a protonation route map of the nylon fiber surface in the method of the present invention; Figure 2 is the TCPP ionization route map in the method of the present invention; Figure 3 The figure is a route map of nylon fiber supporting TCPP ions in the method of the present invention; Figure 4 The present invention is a roadmap for the hydrolysis of nylon fiber-supported TCPP ions; Figure 5 The color of the nylon fiber before supporting TCPP in the method of the present invention; Figure 6 It is the color of the nylon fiber after supporting TCPP in the method of the present invention; Figure 7 The infrared spectra of the nylon fiber prepared by the method of the present invention before and after TCPP is supported; Figure 8 The UV-visible absorption spectra of the nylon fiber prepared by the method of the present invention before and after TCPP is supported; Fig. 9 This is a scanning electron microscope image of the nylon fiber before TCPP is supported in the method of the present invention; Fig.10 This is a scanning electron microscope image of nylon fiber supported with TCPP in the method of the present invention; Fig.11 This is a contact angle test diagram of nylon fiber before supporting TCPP in the method of the present invention; Fig.12 This is a contact angle test diagram of nylon fiber supported TCPP in the method of the present invention; Fig.13 The self-cleaning performance of nylon fiber supported with TCPP on coffee in the method of the present invention; Fig.14 The self-cleaning performance of nylon fiber supported with TCPP on pitaya juice in the method of the present invention. DETAILED DESCRIPTION
[0017] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0018] The method for preparing the visible light self-cleaning nylon fiber of the present invention is specifically implemented according to the following steps: Step 1, soaking nylon fiber in an acetic acid solution, and then stirring at a high temperature to completely protonate the N of the amide bond on the nylon fiber to obtain a modified nylon fiber; The acetic acid solution is a mixture of acetic acid and water in a volume ratio of 1:15; When soaking, heat the acetic acid solution in a water bath to 40~50 o C, the soaking time is 30-40 minutes, so that the nylon fiber is fully wetted, which is conducive to the subsequent protonation reaction; While stirring, heat the acetic acid solution in an oil bath to 100-110 o C, stirring time is 60~80min, so that it can fully react with acetic acid and complete the protonation of N in the amide bond, such as Figure 1 As shown, after protonation, the N on the amide bond carries a positive charge and becomes a reactive site on the nylon fiber, thereby modifying the nylon surface.
[0019] Step 2, dissolving 5, 10, 15, 20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) in a sodium carbonate solution, stirring at room temperature for 30-40 minutes to ensure that TCPP is completely dissolved and TCPP is ionized; The concentration of sodium carbonate solution is 0.1 mol / L; like Figure 2 As shown in the figure, the dissolution process of TCPP is the ionization process of TCPP. After ionization, all the original carboxyl groups (-COOH) in TCPP will become carboxylate ions (-COO-), which are negatively charged and become reactive active sites on the TCPP molecule, which can be used to modify the surface of nylon. Step 3, adding the nylon fiber obtained in step 1 to the mixed solution of step 2, and performing heating reaction under oil bath conditions to load TCPP on the nylon fabric.
[0020] The reaction temperature is 100~110 o C, reaction time is 120~130min; like Figure 3 As shown, due to the electrostatic interaction between the positive and negative charges of the quaternized N on the nylon fiber and the carboxylate ions on TCPP, TCPP will be spontaneously grafted onto the nylon fiber, thereby improving the adhesion of the supported photocatalyst; Step 4, adding acetic acid solution to the nylon fiber obtained in step 3, stirring at a constant temperature to completely acidify it; The acetic acid solution is prepared by mixing acetic acid and water in a volume ratio of 20:20; stirring at room temperature for 30-40 min; like Figure 4As shown in the figure, the TCPP ions supported on the nylon fiber will change from highly reactive carboxylate ions (-COO-) to carboxylic acid groups (-COOH) under the action of acetic acid solution, which reduces the reactivity of the nylon fiber and improves the hydrophilicity of nylon. In addition, since TCPP becomes neutral in this process, there is no repulsive force between molecules. Due to the π-π interaction between TCPP molecules, they will spontaneously self-assemble into TCPP molecular membranes.
[0021] Step 5, washing the nylon fiber obtained in step 4 with deionized water for 4 to 6 times until the pH of the washing solution is 7; Step 6, drying the nylon fiber obtained in step 5 to obtain visible light self-cleaning nylon fiber; Drying temperature is 100~120 o C, drying time is 90~120 min; Example 1 The method for preparing visible light self-cleaning nylon fiber of the present invention comprises the following steps: Step 1: Heat the nylon fiber in a water bath to 40 o C acetic acid solution for 30 min; then the nylon fiber is heated to 100 o C in acetic acid solution and stirred for 60 min; Step 2, dissolving 5, 10, 15, 20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) in a sodium carbonate solution and stirring at room temperature for 30 min; Step 3, adding the nylon fiber treated in step 1 to the mixed solution of step 2, and heating at a constant temperature to load TCPP on the nylon fiber.
[0022] The reaction system was heated in an oil bath and the temperature was maintained at 100 o C, reaction time is 120min; Step 4, adding the nylon fiber treated in step 3 to an acetic acid solution, soaking and stirring at room temperature for 30 minutes; the acetic acid solution is a mixture of acetic acid and water in a volume ratio of 20:20; Step 5, take out the nylon fiber treated in step 4 and wash it with deionized water for 4 times until the washing liquid becomes neutral.
[0023] Step 6: Dry the nylon fiber at a temperature of 100 o C, the drying time is 90 min, and visible light self-cleaning nylon fiber is obtained.
[0024] Example 2 The method for preparing visible light self-cleaning nylon fiber of the present invention comprises the following steps: Step 1: Heat the nylon fiber in a water bath to 45 oC acetic acid solution for 35 min; then the nylon fiber is heated to 105 o C in acetic acid solution and stir for 70 min; The acetic acid solution is a mixture of acetic acid and water in a volume ratio of 1:15; Step 2, dissolving 5, 10, 15, 20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) in a sodium carbonate solution and stirring at room temperature for 35 min; the concentration of the sodium carbonate solution is 0.1 mol / L. Step 3, adding the nylon fiber treated in step 1 to the mixed solution in step 2, and heating at a constant temperature; The reaction system was heated in an oil bath and the temperature was maintained at 105 o C, reaction time 125min.
[0025] Step 4, taking out the nylon fiber treated in step 3, adding acetic acid solution, and stirring at room temperature for 35 minutes; the acetic acid solution is a mixture of acetic acid and water in a volume ratio of 20:20; Step 5, take out the nylon fiber treated in step 4 and wash it with deionized water for 5 times until the washing liquid becomes neutral.
[0026] Step 6: Dry the nylon fiber at a temperature of 110 o C, the drying time is 105 min, and visible light self-cleaning nylon fiber is obtained.
[0027] Example 3 The method for preparing visible light self-cleaning nylon fiber of the present invention comprises the following steps: Step 1: Heat the nylon fiber in a water bath to 50 o C acetic acid solution for 40 min; then the nylon fiber is heated to 110 o C in acetic acid solution and stirred for 80 min; Step 2, dissolving 5, 10, 15, 20-tetrakis(4-carboxyphenyl)porphyrin (TCPP) in a sodium carbonate solution and stirring at room temperature for 40 min; Step 3, adding the nylon fiber treated in step 1 to the mixed solution in step 2, and heating at a constant temperature; The reaction system was heated in an oil bath and the temperature was maintained at 110 o C, reaction time 130 min.
[0028] Step 4, taking out the nylon fiber treated in step 3, adding acetic acid solution, and stirring at room temperature for 40 minutes; the acetic acid solution is a mixture of acetic acid and water in a volume ratio of 20:20; Step 5, take out the nylon fiber treated in step 4 and wash it with deionized water for 6 times until the washing liquid becomes neutral.
[0029] Step 6: Dry the nylon fiber at a temperature of 120 o C, the drying time is 120 min, and visible light self-cleaning nylon fiber is obtained.
[0030] Example 4 The photocatalytic pollutant degradation performance results of the visible light self-cleaning nylon fibers of Examples 1-3 of the present invention are shown in Table 1; Table 1 Photocatalytic pollutant degradation performance of the self-cleaning nylon fibers of Examples 1-3
[0031] Note: All experiments were carried out at room temperature of 20°C, pH value of 7, and xenon lamp power of 500W.
[0032] The above tests were conducted in accordance with the national standards in the field of photocatalysis, which are as follows: GB / T23762-2009 (Test method for purification of aqueous solution system of photocatalytic materials). As shown in Table 1, the degradation effect of nylon fiber supported by TCPP in 60 min was slightly lower than that of rhodamine, while that of methylene blue and methyl orange reached more than 80%, and the effect increased significantly. Moreover, the degradation effect of nylon fiber supported by TCPP decreased little after 5 cycles, indicating that it has high stability.
[0033] Example 5 The nylon fiber prepared by the method of the present invention is characterized as follows: (1) The color of nylon fiber before supporting TCPP is off-white. Figure 5 As shown, it turns dark purple after loading. Figure 6 As shown, since the color of pure TCPP is dark purple, it can be inferred that TCPP is loaded on the surface of nylon fibers.
[0034] (2) Nicolet 5700 Fourier transform infrared spectrometer was used to measure the structure of nylon fiber before and after TCPP was supported. Figure 7 As shown in the figure, after loading, the infrared has a more obvious peak in the 3500 band, because the main absorption band of the NH bond in the TCPP molecule is at 3000-3500, and there are peaks at 1000, 1500 and 1750, which correspond to the three bands of the C=O double bond absorption area in the TCPP molecule. At the same time, the absorption band of the carboxyl group in the TCPP molecule is mainly at 650. In summary, TCPP has been successfully loaded on nylon fibers.
[0035] (3) The light response ability of nylon fiber before and after TCPP loading was measured using UV-2450 ultraviolet visible light photometer. Figure 8As shown in the figure, it can be seen that the response of nylon fiber in the visible light region is significantly enhanced after TCPP loading, indicating that the loading and self-assembly of TCPP greatly improve the response of nylon fiber in the visible light region, which is beneficial to improving the visible light photocatalytic performance of nylon fiber.
[0036] (4) Fig. 9 and Fig.10 The scanning electron microscope images of nylon fiber before and after TCPP was supported. It can be seen from the figure that the surface of the nylon fiber changed from smooth to very rough, which further illustrates the successful loading of TCPP.
[0037] (5) The contact angle of nylon fiber before and after TCPP was supported was measured using the contact angle meter DSA100E. Fig.11 , Fig.12 As shown in the figure, due to the hydrophilicity of TCPP carboxyl group, the contact angle of nylon fiber supported by TCPP becomes larger.
[0038] Example 6 0.5 mL of coffee and dragon fruit juice (50 mg / L) were dripped onto the surface of nylon fabric with a size of 5 cm × 5 cm using a dropper. The self-cleaning performance of nylon fiber supported by TCPP was compared with that of unmodified nylon fiber as a control. The contaminated fabric was irradiated under a 500 W xenon lamp, with the fabric 20 cm away from the light source for 60 min. Fig.13 and Fig.14 It can be seen that the degradation effect of nylon fiber-supported TCPP on coffee and dragon juice is significant, and the effect decreases slightly after 5 cycles, indicating that it has high stability.
Claims
1. A method for preparing visible light self-cleaning nylon fiber, characterized in that: Follow the steps below to implement it: Step 1, soaking nylon fiber in an acetic acid solution, and then stirring at a high temperature to obtain modified nylon fiber; Step 2, dissolving 5, 10, 15, 20-tetrakis(4-carboxyphenyl)porphyrin in a sodium carbonate solution and stirring to ionize TCPP; Step 3, adding the nylon fiber obtained in step 1 to the mixed solution of step 2, and heating the mixture in an oil bath for reaction; Step 4, adding acetic acid solution to the nylon fiber obtained in step 3, stirring to acidify it thoroughly; Step 5, washing the nylon fiber obtained in step 4 with deionized water until the pH of the washing solution is 7; Step 6, drying the nylon fiber obtained in step 5 to obtain visible light self-cleaning nylon fiber.
2. The method for preparing the visible light self-cleaning nylon fiber according to claim 1, characterized in that: In step 1, the acetic acid solution is prepared by mixing acetic acid and water in a volume ratio of 1:15; during soaking, the acetic acid solution is heated in a water bath to 40-50 o C, soaking time is 30~40min; while stirring, heat the acetic acid solution in an oil bath to 100~110 o C, stirring time is 60~80min.
3. The method for preparing the visible light self-cleaning nylon fiber according to claim 1, characterized in that: In step 2, the concentration of the sodium carbonate solution is 0.1 mol / L; and the stirring time is 30 to 40 min.
4. The method for preparing the visible light self-cleaning nylon fiber according to claim 1, characterized in that: In step 3, the reaction temperature is 100-110 o C, reaction time is 120~130min.
5. The method for preparing the visible light self-cleaning nylon fiber according to claim 1, characterized in that: In step 4, the acetic acid solution is prepared by mixing acetic acid and water in a volume ratio of 20:20; the stirring time is 30 to 40 minutes.
6. The method for preparing the visible light self-cleaning nylon fiber according to claim 1, characterized in that: In step 6, the drying temperature is 100-120 o C, drying time is 90~120min.
7. Nylon fiber prepared by the method for preparing visible light self-cleaning nylon fiber according to any one of claims 1 to 6.
8. Use of the visible light self-cleaning nylon fiber according to any one of claims 1 to 6 in photocatalytic degradation of pollutants.
Citation Information
Patent Citations
Porous membrane matrix-based monodisperse porphyrin visible-light-driven photocatalyst and preparation method thereof
CN107930692A
Method for preparing tetracarboxyphenyl porphyrin supramolecular photocatalyst and application thereof
CN108014850A
Rotational tidal stream power generation device
KR102478786B1